The Effect Components and Mechanisms of Action of Cimicifugae Rhizoma in the Treatment of Acute Pneumonia - Zhu J; Huang Y; Ye C; Deng X; Zou Y; Yuan E; Chen Q (Journal of Inflammation Research)
Jing Zhu,1 Yiming Huang,1,2 Chao Ye,3 Xiaoxia Deng,1,2 Yuxuan Zou,1,2 En Yuan,2 Qi Chen2 1Research Center for Chinese Medicine Resources and Ethnic Minority Medicine, Jiangxi University of Chinese Medicine, Nanchang, People’s Republic of China; 2School of Pharmacy, Jiangxi University of Chinese Medicine, Nanchang, People’s Republic of China; 3The Affiliated Hospital of Jiangxi University of Chinese Medicine, Nanchang, People’s Republic of ChinaCorrespondence: Jing Zhu, Research Center for Chinese Medicine Resources and Ethnic Minority Medicine, Jiangxi University of Chinese Medicine, Nanchang, People’s Republic of China, Tel +86-13755654318, Email 277836041@qq.comObjective: The main objective of this study was to elucidate the effector material basis of Cimicifugae Rhizoma (CR) for the treatment of acute pneumonia (AP) and to explore the potential mechanisms underlying the anti-AP effects of these active components in a lipopolysaccharide (LPS)-induced inflammation model of lung epithelial cells.Methods: Chemical components were identified using ultra-performance liquid chromatography-quadrupole-time-of-flight tandem mass spectrometry (UPLC-TOF-MS), and a CR component library was subsequently established based on a combination of databases and available literature. Bioinformatics techniques were used to construct “component-target” and “protein-protein interaction (PPI)” networks, and the potential active components and core targets screened according to degree value, followed by molecular docking and in vitro experiments for verification. Inflammation was induced in normal human lung epithelial cells using lipopolysaccharide (LPS) to mimic the occurrence of AP.Results: In total, 122 CR components were identified. The therapeutic effects of potential active components against AP were associated with 147 targets involving 165 signaling pathways. Molecular docking experiments revealed the strong affinity of N-cis- feruloyltyramine, ferulic acid, cimifugin, and isoferulic acid for core AP-associated targets. In vitro cellular experiments showed that the above compounds and CR alcoholic extracts inhibited the expression of inflammatory factors in the following order: isoferulic acid > cimifugin > CR alcoholic extract > N-cis-feruloyltyramine > ferulic acid.Conclusion: N-cis- feruloyltyramine, ferulic acid, cimifugin, and isoferulic acid were the effector components of CR with activity against AP. These compounds potentially co-regulate the IL-6/JAK/STAT3 and TLR4/IL-1β-IRAK pathways through the inhibition of cytokines such as IL-6, TNF-α, and IL-1β, and downregulation of P-STAT3, TLR4, PIK3CA, and NF-κB involved in TLR4/IL-1β-IRAK/NF-κB and PI3K-Akt signaling pathways to exert therapeutic effects on AP.Keywords: acute pneumonia, molecule docking, lung epithelial cells, LPS, signaling pathway